Jainul Abideen’s approach to Qur’anic interpretation - Seyed Ibrahim, Syed Alaudeen; Ushama, Thameem (IIUM Press, International Islamic University Malaysia, 2017)
Jainul Abideen is a founder of Tamil Nadu Tawhid Jamaat (TNTJ) which has the largest number of followers among Tamil speaking Muslims in Tamil Nadu and other parts of the world. He has interpreted the Qur’Én and ×adÊth books. His views differ from the mainstream interpretations of well-established scholars on various issues, such as siÍr, evil eye, understanding of the ×adÊth, etc. He gives fatÉwÉ on ÎiÍr and evil eye but they differ from other scholars. Although some scholars of Tamil Nadu criticise his controversial views, it has drawn very little research attention in the academia, and remained unstudied in India and beyond. This book focuses on Jainul Abideen’s life and interpretations of the Qur’Én and ×adÊth on selected issues. Using analytical and critical methods, the study scrutinizes the views of Jainul Abideen based on his booklets, public speeches, video tapes and articles. In addition, the study analyses the interpretations and views of the pioneering scholars of Ahl al-Sunnah wa al-JamÉÑah to compare the views of Jainul Abideen. Thus, the authors examine the differences between the views of Jainul Abideen and the majority of scholars of Ahl al-Sunnah wa al-JamÉÑah. This study notices that the arguments and views of Jainul Abideen on those selected issues are similar to the views of MuÑtazilah, a controversial sect in the Muslim history.